From Nationalism to Islamic Resistance: Shamil Basayev and the Transformation of Chechen Struggle during the First Chechen War (1994–1996) - Muhamad Shamil Bashayev; Aip Aly Arfan (Universitas Islam Negeri Sumatera Utara, 2026)
The First Chechen War (1994–1996) marked a significant transformation of the Chechen resistance from an ethno-nationalist movement into a struggle increasingly framed through Islamic narratives. While previous studies have largely focused on security, nationalism, and political violence, limited attention has been paid to the role of individual actors in shaping this ideological shift. This article examines the role of Shamil Basayev in the transformation of the Chechen resistance from nationalism to Islamic resistance during the First Chechen War. This study employs a qualitative historical approach combining historical methods, literature review, and Critical Discourse Analysis (CDA). Data were collected from academic publications, historical documents, media archives, and other secondary sources related to the conflict. The findings reveal that the early phase of the Chechen resistance was primarily driven by nationalist aspirations for independence and self-determination. However, prolonged warfare, military asymmetry, limited international support, and the influence of transnational Islamic networks contributed to a gradual ideological transformation. Shamil Basayev emerged as a key agent of change by incorporating Islamic symbols, narratives of jihad, and religious legitimacy into the resistance strategy. This transformation was reflected in shifts in legitimacy, mobilization, and collective identity. The study concludes that the Islamization of the Chechen resistance was a historically constructed process shaped by local political conditions, global Islamic influences, and the agency of key actors. It demonstrates how religion functioned as a dynamic source of legitimacy and political mobilization in modern conflicts.